Long-term impacts of 48-h water and feed deprivation on blood and performance responses of grazing Bos indicus Nellore heifers - Abreu, Mateus J.I. [UNESP]; Marques, Rodrigo S.; Cidrini, Iorrano A. [UNESP]; Batista, Luis H.C. [UNESP]; Ferreira, Igor M. [UNESP]; Oliveira, Karla A. [UNESP]; Cruz, Vinicius A.; Limede, Arnaldo C.; Sousa, Luciana M. [UNESP]; França, Matheus Q.S.; Bísio, Gustavo H.M.; Siqueira, Gustavo R. [UNESP]; et al. (Oxford University Press (OUP), 2024)
The study investigated the effects of 48-h water and feed deprivation on blood and the performance of grazing Nellore (Bos indicus) heifers. Twenty-four Nellore heifers (initial body weight [BW] = 238 ± 10 kg; age = 16 ± 2 mo), were ranked by initial BW and age and randomly assigned to one of the two treatments: (1) grazing animals with free access to pasture, water, and mineral-mix (CON; n = 12), or (2) the same grazing conditions but deprived of pasture, water, and mineral-mix for 48 h (DPR; n = 12). The paddocks consisted of Urochloa brizantha cv. Marandu, using a continuous and fixed stocking rate. The experiment lasted 225 d, with the first 14 d considered as the adaptation period (days −14 to −1) and the subsequent 211 d as the evaluation period (days 0 to 211). From days 0 to 2, treatments were applied by keeping the DPR heifers in pens and reintegrating them into the experimental area after a 48-h water and feed deprivation. Individual full BW was recorded on days −14, −13, −1, before (day 0) and after (day 2) treatment application, and on days 6, 11, 12, 41, 42, 210, and 211. Blood samples were collected in the morning on days 0, 2, 6, 12, and 211. A treatment effect was detected (P < 0.001) for shrink BW from days 0 to 2, which was greater (P < 0.001) in DPR vs. CON heifers. Subsequently, DPR animals were lighter (P < 0.001) compared with CON heifers by the end of the deprivation period (day 2). From days 4 to 211, DPR was lighter (P < 0.001) compared with CON heifers after treatment application and for the entire experimental period. In the first 10 d after treatment application (days 2 to 12), DPR heifers showed a partial compensatory average daily gain (ADG; P < 0.001) compared with CON heifers, while no significant differences were observed in ADG between the treatments from days 12 to 42 and 42 to 211 (P > 0.420). Overall ADG (days 2 to 211) was greater (P < 0.001) for DPR vs. CON heifers. All serum variables, except AST, were higher (P < 0.001) in DPR than in CON heifers on day 2 after treatment application. Our study demonstrates that grazing Nellore heifers subjected to 48-h water and feed deprivation experienced significant alterations in their blood metabolites and BW immediately after the stressful event. Although the deprived heifers partially compensated for their BW loss in the early days post-deprivation, they remained 12 kg lighter than the non-deprived animals throughout the production cycle. Routine management practices in beef cattle operations, such as shipping and receiving at feedlot facilities, may cause the animals to go without food and water for extended periods. The findings of this study reveal that Nellore (Bos indicus) heifers subjected to a 48-h water and feed deprivation exhibited substantial changes in their blood metabolites and lost 14.6% of their body weight by the completion of the deprivation period. Although the deprived heifers showed a partial compensatory increase later, they remained 12 kg lighter than the non-deprived heifers throughout the production cycle.
Keywords: blood metabolites; Bos indicus; feed and water deprivation; grazing; Nellore heifers; performance